Beyond "Place": Translocal Placemaking of the Hmong Diaspora. (June 2015) - Rios, Michael; Watkins, Joshua
For many migrants and refugees, place provides a common sense of territorial identity despite these groups having roots elsewhere. Using the case of the Hmong diaspora, the following calls for a reconsideration of how place is theorized in planning and introduces the term "translocal placemaking" to better reflect new social formations and the overdetermination of locality. This relational conception of place captures the complexity of spatial and temporal relations as locales are not isolated from one another and draws attention to the various entanglements that historically shape spatial practices including the memories and ties to extralocal places.